Contribution to the knowledge on the Palaearctic and Oriental taxa of the Meganola s.l. (Lepidoptera, Noctuoidea, Nolidae, Nolinae) generic complex with descriptions of 4 new genera and 11 new species - László, Gyula M.; Ronkay, Gábor; Ronkay, László (Zootaxa, 2015)
Present paper contains the descriptions of four new genera distinguished from the collecting genus Meganola s.l. (Hampsonola, Wittonola, Fragilonola and Maculonola gen. n.) and 11 new species (Meganola pseudobasalactifera, Hampsonola diehli, H. subbasirufa, H. angustifasciata, H. stueningi, H. micra, Wittonola latifasciata, Nanola rothschildi, Fragilonola fragilis, F. parentela and Maculonola dolokmerangirensis spp. n.) from South East Asia. Based on genital morphology the concept of the genus Nanola is extended, involving several species treated earlier as Meganola. Meganola yakovlevi László, Ronkay & Ronkay, 2010 is synonymised with M. tetrodon (de Joannis, 1928), and M. pekarskyi László, Ronkay & Ronkay, 2014 is synonymised with Nanola liaoningensis (Han & Li, 2008), syn. n. 45 new combinations and 2 new stati are established. With 48 colour photos and 42 genitalia figures.